Empowering Communities: A Homestay Management Strategy In Sukajadi Village, Bogor Regency - Sri Pujiastuti; Roels Ni Made Sri Puspadewi; Dikki Z. Choesrani (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze and formulate a development strategy for homestays in Sukajadi Tourism Village, Tamansari District, Bogor Regency, using the SWOT analysis framework. Employing a descriptive qualitative approach, data were collected through in-depth interviews and field observations involving six homestay units and key stakeholders, including the Chairman of the Tourism Awareness Group (Pokdarwis). The findings reveal that the internal condition of homestay management in Sukajadi Village is weak (total IFAS score: 1.74), primarily due to deficiencies in hygiene, facility standards, safety, access to information, and unprofessional operational and financial management. Although the homestays possess a key strength in the form of the owners’ hospitality, these weaknesses significantly limit the ability to leverage external opportunities such as growing tourist interest in authentic experiences and government support. From an external perspective, the homestays demonstrate a moderately responsive position (total EFAS score: 2.46) but face serious threats from competition with modern accommodations and rising tourist expectations. The study underscores the urgency of improving service quality, strengthening management capacity, and enhancing human resources through continuous training. Collaborative efforts among homestay owners, Pokdarwis, and local government are crucial to establish minimum operational standards, improve infrastructure, and promote authentic local experiences to achieve sustainable homestay development and meaningful community empowerment. Keywords: Homestay, Community Empowerment, SWOT Analysis, Tourism Village